La voluntat de comunicar com a objecte primordial en l'aprenentatge d'una L2 - Marí, Isidor (Caplletra. Revista Internacional de Filologia, 2008)
Although evidence has shown that psychosocial factors have a decisive influence in second language learning, it has not been highlighted the importance they have regarding educational practice, the design of learning programs or teacher training.The model known as Willingness to Communicate, developed by MacIntyre et al. (1998) from numerous empirical works, points at the factors that favor authentic use in the learning of a second language and the relationships among them. The goal ofa language course can not be limited to developing communicative competence but has to be aimed at increasing the willingness to communicate actively. Following this theoretical model, one of its authors, Zoltán Dörnyei (2001), has devoted one of his books to the development of practical strategies of motivation in the language classroom. These approaches are specially useful for contexts of linguistic concurrence like ours, especially at a moment in which school multilingualism is promoted.